Analysis of the Effect of Current Harmonic Induced Heating on Transformer Ageing - Tamang, Rojan; Shrestha, Bijaya; Kashichhwa, Aasma; Gautam, Suman; Bhattarai, Umanga; Gautam, Rupesh (Journal of Science and Engineering, 2025)
Due to advanced control and increased efficiency, the concentration of power electronics-based equipment is increasing rapidly in recent times causing higher injection of nonlinear current to the system, affecting various equipment in the power system. The ageing of a transformer depends primarily on the hotspot temperature. However, the hotspot temperature is influenced by the loading condition of the transformer and the nature of the current drawn by the loads connected to it. In this study, the loss of life of transformers due to non-linear current is assessed. For the analysis, the non-linear current with different THD (4.48%, 10.55%, 15.22%, 24.09%, and 30.79%) is created in the laboratory and the transformer life under varying loading level (80%, 90%, 100%, and 110%) with these currents is evaluated. The parameters of a 3000 kVA transformer are used for analysis, and nonlinear current is generated by connecting a rectifier load to a small UPS transformer. The analysis is performed by estimating the temperature of the hotspot and calculating the acceleration factor of ageing (FAA) and the percentage of loss of life (LoL). It is found from the study that a higher harmonic content in the system’s current leads to larger loss of life of the transformer, and degradation in the transformer’s life occurs even if the THD of the current signal is within the standard limit.